Respiratory Function And Muscular Capacity In Old Adults: The Aga@4Life Project - Daniel Alexandre Dias Pedroso; Telmo Pereira; Jorge Conde (Brazilian Society of Geriatrics and Gerontology, 2024)
INTRODUCTION: Age-related muscle changes, translated into a decrease both in muscle imass and functionality, are determinants of a decrease in strength and resistance to exercise in older adults. OBJECTIVE: To correlate the loss of muscle mass and functionality with the respiratory function in older adults. METHODS: Cross-sectional study including 18 volunteers with age above 65 years (13 women and 5 men) included in the AGA@4life Project. All participants performed functional respiratory tests with an Flowhandy ZAN 100 spirometer, and handgrip strength was assessed with an appropriate dynamometer. Nutritional profile was assessed and body composition was evaluated via bioimpedance. RESULTS: There was a significant association between the percentage of lean mass and several spirometric parameters, namely the FEV1, FVC, PEF25, PEF50, PEF25/75 and PEF. Significant associations were also found with the self-efficacy for exercise and the same respiratory parameters. A significant and positive correlation was observed between the percentage of lean mass and handgrip strength. CONCLUSIONS: The results show an association between respiratory function and functional and clinical parameters characteristic of sarcopenia, suggesting common pathophysiological mechanisms in the limitation observed with the worsening of these parameters.